The Implementation of Lesson Study Based Learning Management and the Effect toward Students’ Activeness in Lecturing - Imam Gunawan (JPP (Jurnal Pendidikan dan Pembelajaran), 2017)
The purpose of this research was to: (1) describe the process of lesson study based instructional management; and (2) enhance students’ activity in lecturing by implementing the lesson study based instructional management. The method used in this research was descriptive qualitative and classroom action research, which were implemented with two cycles, the first cycle and the second cycle. The research instruments were the lesson study observation sheet and students’ activity observation sheet during the learning process. The results showed that: (1) the process of lesson study based instructional management was a cyclical process involving the development of the lesson plans, the implementation of learning (do, open class), and the evaluation of learning (see), and (2) there was an improvement in terms of students’ activeness in following the lecturing activity when lesson study based instructional management was implemented.